Intrauterine transfusion under fetal analgesia: the evaluation of perinatal outcomes - Lanna, Mariano; Casati, Daniela; Bianchi, Chiara; Faiola, Stefano; Laoreti, Arianna; Cavigioli, Francesco; Savasi, Valeria; Lista, Gianluca (Frontiers in Pain Research, 2024)
IntroductionIntrauterine transfusion is the treatment for fetal anemia resulting from maternal alloimmunization, infections (parvovirus B19 and cytomegalovirus), single demise of a monochorionic twin, chorioangioma, and other rare conditions. Fetal analgesia is mandatory to reduce movement and pain perception during the procedure. This study aims to evaluate perinatal outcomes for such procedures, following the routine use of fetal analgesia in our clinical practice.Materials and methodsRetrospective analysis of cases from 2009 to 2022, including all confirmed fetal anemia with fetal blood sampling. After fetal analgesia, Rh-negative concentrated red blood cells were transfused, with ultrasonographic follow-up 24 h and 1 week later. In case of suspected brain lesion, magnetic resonance imaging was performed. Elective delivery was considered in case of persistent anemia after 34 weeks. Post-natal follow-up and comprehensive obstetric and perinatal outcomes data were collected.ResultsAltogether 59 anemic fetuses were included, with 34 (57.6%) being hydropic. The causes of anemia were maternal alloimmunization (22, 37.3%), infections (13, 22%), monochorionicity (10, 16.9%), rare conditions (9, 15.3%), and two chorioangiomas (3.4%). The median gestational age at the procedure was 25.2 weeks (18–32 weeks), with no related preterm premature rupture of membranes (<48 h), or side effects from fetal analgesia. Gestational age at delivery was 33 weeks (26–41 weeks), with survival rate of 90%. There were four fetal demises, two termination of pregnancies, and eight neonatal deaths due to persistent severe anemia after preterm delivery. The main contributors to adverse outcome were the type of anemia, and the management with a preterm delivery.ConclusionIntrauterine transfusion of red blood cells under analgesia is safe, with low incidence of obstetric complication.